PENINGKATAN KREATIVITAS DAN INOVASI DALAM PENGEMASAN ROTI BAGI UMKM DI KELURAHAN SAWAH LUHUR KECAMATAN KASEMEN KOTA SERANG - Suflani, Suflani; Komarudin, Mochamad Fahru; Suganda, Ahmad; Purwatisari, Ani; Rezky, Reditya Putra Octevio; Amri, Saipul; Darmawan, Muhamad Rival Nur; Andini, Andini (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This community service activity aims to increase creativity and innovation in packaging bread products for MSMEs in Sawah Luhur Village, Kasemen District, Serang City. Bakery MSMEs in this region face significant challenges related to packaging, which hinders product marketing and competitiveness. This program includes intensive training on packaging design, modern packaging technology, and digital innovations such as QR codes and Augmented Reality (AR). Apart from that, the training also focuses on the use of environmentally friendly packaging materials and circular economy concepts. The results of the activity showed that the participants succeeded in creating a more attractive and functional packaging design. This increase in understanding and skills has a positive impact on sales of MSME products. This program also underlines the importance of collaboration between academics, practitioners and government in encouraging MSME innovation in the digital era